Produção e caracterização de nanocompósitos de PVDF, MWCNT e óxidos metálicos como biomaterial para aplicações biomédicas - Esther Lorrayne Machado Pereira (2021)
The production of hybrid materials of polymeric matrix reinforced with loads of technological interest is a strategy to obtain lightweight materials with differentiated properties. Poly(vinylidene fluoride) polymer (PVDF) is known for its properties, properties, electromechanical and biocompatibility. In this work, PVDF nanocomposites and Multiple Wall Carbon Nanotubes (MWCNT), plus Barium Sulfate (BaSO4) and Bismuth Oxide (Bi2O3), were cut and characterized, with their own as implant biomaterial. The techniques of X-rays (XR) and Computed Tomography (CT). In order to visualize in Magnetic Resonance (MRI) exams, the implanted nanomaterial needs to be able to produce positive contrast and not to generate artifacts in the image, considering these characteristics a base of PVDF plus Magnetite (Fe3O4) were synthesized. In the literature, the use of visualization of post-surgery implants by noninvasive methods to monitor inflammatory processes, displacement of prostheses and possible contraction of the material is indicated. In this sense, it is expected to meet this demand by producing new nanocomposite materials, studying their thermal, mechanical properties and their visibility in diagnostic imaging exams. Samples of PVDF/Bi2O3 (1:1), without the presence of MWCNT, demonstrated attenuation compatible with that theoretically predicted by the National Institute of Standards and Technology (NIST), estimated at 33.49%. Qualitative and quantitative tests using Medical Image Processing, Analysis and Visualization software (MIPAV) reinforce the potential for visualizing X-ray images. On CT scans as they are viewed again. Attenuation coefficient calculations demonstrate that the increase in thickness is related to the increase in energy for an absorption range that can be attenuated by the composite. MRI images indicate that smaller proportions of Fe3O4 favor the formation of images with better definition of details, with the In/Out technique used for qualitative analysis and Nuclear Magnetic Resonance (NMR) Spectroscopy used for quantitative analysis.